Oxidative stress, epigenetic regulation and pathological processes of lens epithelial cells underlying diabetic cataract - Guo, Zaoxia; Ma, Xiaopan; Zhang, Rui Xue; Yan, Hong (Advances in ophthalmology practice and research, 2023)
Cataract is a blinding disease worldwide. It is an age-related disease that mainly occurs in people over 65 years old. Cataract is also prevalent in patients with diabetes mellites (DM). The pathological mechanisms underlying diabetic cataract (DC) are more complex than that of age-related cataract. Studies have identified that polyol pathway, advanced glycation end products (AGEs) and oxidative stress are the primary pathogenesis of DC. In recent years, molecular-level regulations and pathological processes of lens epithelial cells (LECs) have been confirmed to play roles in the initiation and progression of DC. A comprehensive understanding and elucidation of how chronic hyperglycemia drives molecular-level regulations and cytopathological processes in the lens will shed lights on the prevention, delay and treatment of DC. Excessive glucose in the lens enhances polyol pathway and AGEs formation. Polyol pathway causes imbalance in the ratio of NADPH/NADP+ and NADH/NAD+. Decrease in NADPH/NADP+ ratio compromises antioxidant enzymes, while increase in NADH/NAD+ ratio promotes reactive oxygen species (ROS) overproduction in mitochondria, resulting in oxidative stress. Oxidative stress in the lens causes oxidation of DNA, proteins and lipids, leading to abnormalities in their structure and functions. Glycation of proteins by AGEs decreases solubility of proteins. High glucose triggered epigenetic regulations directly or indirectly affect expressions of genes and proteins in LECs. Changes in autophagic activity, increases in fibrosis and apoptosis of LECs destroy the morphological structure and physiological functions of the lens epithelium, disrupting lens homeostasis. In both diabetic animal models and diabetics, oxidative stress plays crucial roles in the formation of cataract. Epigenetic regulations, include lncRNA, circRNA, microRNA, methylation of RNA and DNA, histone acetylation and pathological processes, include autophagy, fibrosis and apoptosis of LECs also involved in DC.